Eco-Mosque and Climate Change Campaign: An Ecolinguistic Study and Philosophy of Islamic Law - Syaiful Amri; Zezen Zainul Ali; Muh Zaitun Ardi; Nadyatul Hikmah Shuhufi (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This study examines the concept of eco-mosques as a campaign to strengthen the ecological movement in contemporary Islamic discourse. Ecological campaigns have also been carried out through digital platforms such as the Instagram account @ecomasjid.id, which seeks to reinterpret Islamic values to build ecological awareness through social media campaigns. This study analyzes the construction of eco-theological messages disseminated through the Instagram account @ecomasjid.id. Using a netnographic approach, data was collected from posts, text descriptions, and visual material, then analyzed through the frameworks of ecolinguistics, ecosophy, and maqāṣid al-sharī‘ah. The results show that @ecomasjid.id places ecological responsibility as an integral part of Islamic ethics, emphasizing environmental concern as a manifestation of faith. Maqāṣid principles such as the preservation of life, reason, and property are not presented descriptively, but rather articulated in persuasive narratives that link sustainability with spirituality and community welfare. These findings show that Islamic digital activism is capable of reconstructing classical fiqh concepts to respond to global ecological challenges. Theoretically, this research enriches the study of the transformation of digital da'wah and the integration of maqāṣid values into the ecological consciousness of Muslims.